038 Pregnancy outcomes in patients treated with ocrelizumab. Issue 6 (27th May 2022) - Brex, Peter; Oreja-Guevara, Celia; Wray, Sibyl; Buffels, Regine; Zecevic, Dusanka; Vukusic, Sandra
Abstract : Background: Ocrelizumab is approved for the treatment of relapsing forms and primary progressive multiple sclerosis (MS). Methods: We report analyses of pregnancies in women who received ocrelizumab in clinical trials/post- marketing sources up to 31/03/2019. Contraceptive requirements for women of childbearing potential were per label (during treatment and for 6/12 months after the last infusion) or adapted in clinical trials (two methods for 6 months or until 48 weeks after the last infusion/until B-cell repletion [whichever longer]). Foetal exposure was defined as the last infusion occurring within 3 months of conception or during pregnancy if the conception date was unknown. Results: A total of 362 ocrelizumab-exposed pregnancies in women with either MS (N=267), rheumatoid arthritis/systemic lupus erythematosus (N=33) or an unknown indication (N=62) have been reported. Of the 267 pregnancies in women with MS, 118 were considered to have foetal exposure, 47 did not have foetal exposure and 102 had unknown foetal exposure. Preliminary pregnancy outcomes in MS patients include: 62 live births, 86 ongoing pregnancies, 25 elective abortions, 10 spontaneous abortions, 1 stillbirth, 3 ectopic pregnancies, 22 lost to follow-up and 58 unknown/unreported outcomes. Conclusions: Cases to date do not suggest an increased risk of adverse pregnancy/foetal outcomes with ocrelizumab. p.brex@nhs.net